Ulcerating rheumatoid nodule of the vulva. Issue 1 (January 1996) - Appleton, M A; Ismail, S M
Abstract : A case of an ulcerating rheumatoid nodule of the vulva in a 76 year old woman with rheumatoid arthritis complicated by Felty's syndrome is reported. The patient presented with a mass in the vulval region. On clinical examination, she had an ulcerated mass associated with inguinal lymphadenopathy. These findings resulted in a clinical diagnosis of invasive carcinoma of the vulva and an excision biopsy was carried out. On microscopic examination, the lesion showed the characteristic features of a rheumatoid nodule with ulceration of overlying epidermis. Adjacent vessels showed inflammation and fibrinoid necrosis of their walls suggestive of a vasculitis. Awareness of the possibility of ulceration in rheumatoid nodules may facilitate diagnosis and avert unduly aggressive treatment.